2014
DOI: 10.5005/jp-journals-10024-1537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of a Home-bleaching Agent on the Surface Characteristics of Indirect Esthetic Restorative Materials: Part I—Roughness

Abstract: Background Pressing esthetic demands of good looking make people undergo bleaching procedures. However, the effect of bleaching agents on esthetic restorative materials with different surface preparations has been poorly studied. Aim The aim of this study was to examine the effect of a homebleaching agent (carbamide peroxide: CP 38%) on the surface roughness of the polished fiber reinforced composite (FRC), overglazed, autoglazed, or polished ceramic samples. Materials and methods Twenty standardized cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The mean surface roughness (Ra) values for different ceramics in ascending order were 0.42 (±0. 19) for LDS, 0.97 (±0.34) for ZLS, and 1.90 (±0.72) for PIC. Multiple linear regression showed that the overall regression was statistically significant (R 2 = 0.734, F = 10.9, and p < 0.001).…”
Section: Surface Roughnessmentioning
confidence: 95%
See 1 more Smart Citation
“…The mean surface roughness (Ra) values for different ceramics in ascending order were 0.42 (±0. 19) for LDS, 0.97 (±0.34) for ZLS, and 1.90 (±0.72) for PIC. Multiple linear regression showed that the overall regression was statistically significant (R 2 = 0.734, F = 10.9, and p < 0.001).…”
Section: Surface Roughnessmentioning
confidence: 95%
“…14 A number of studies showed that the effects of bleaching on surface properties such as surface roughness and microhardness of different ceramic materials are not significant. 11,[15][16][17][18] On the other hand, some studies have shown a significant negative effect on surface roughness, 13,14,[19][20][21][22][23][24] gloss, 14 and microhardness 25 suggesting that these restorations should be carefully protected during bleaching procedures. The effects concerning surface roughness have been shown to be influenced by the type of surface treatment of the ceramic prior to the bleaching treatment (e.g.…”
Section: The Effect Of Bleaching On Surface Roughness and Gloss Of Di...mentioning
confidence: 99%